Did Fintech increase Financial Inclusion in Africa ? - Adam Sa'ad, Auwal; Vatimetou, Mokhtar; Salina, Kassim; Anwar, Hasan Othman (2021)
Artificial intelligence (AI) is a revolutionary technology that has been used tremendously in the contemporary industrial revolution 4.0 technology. AI has played a crucial role in accelerating financial inclusion rate by easing the use of financial products. From the African perspectives, there is a very few notable uses of AI technologies in the banking and finance industry but such uses are not advance in nature. Therefore, this paper attempts to study the role of AI for financial inclusion in some selected African countries. This paper is a conceptual study that uses a systematic literature review. This study uses variuos and most recent published papers obtained from different online databases (mainly Scopus, Elsevier science direct, Tailor & Francis, EBSCO, and JSTOR) to investigate the conceptual and empirical role of AI on financial inclusion and poverty in some selected African countries. The study reveals that the most common fintech tools used in Africa are mobile money and crowdfunding. Therefore, some recommendations are provided for governments and policymakers to instigate techniques that will enhance digital financial inclusion including the utilization of Artificial Intelligence for the purpose of poverty alleviation in Africa